Prevention of Irritant Contact Dermatitis Due to Hand Hygiene in The Era of COVID 19 Pandemic - Nopriyati; Damai Trilisnawati; Yulia Farida Yahya; Mutia Devi; Theresia L. Toruan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Irritant contact dermatitis (ICD) is an inflammatory epidermal disorder associated with physical or immunological provocation that results in impaired skin barrier. The prevalence of ICD is found to be 17-30% in healthcare workers compared to general population. The first-line management strategies of ICD is based on prevention. Intensive hand cleansing is one of the causes of ICD. Hand hygiene is general term that refers to any action of hand cleansing. Hand hygiene practices include hand washing and hand rubbing with antiseptics. Hand hygiene is the most effective preventive measure in preventing infection control, especially in the era of coronavirus (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) since December 2019. This disease is transmitted through inhalation or contact with infected droplets. Prevention and mitigation actions are key in controlling infection.